2015
DOI: 10.1007/s13369-015-1788-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior and Passivation of Cu–30Zn Alloy in Aqueous NaOH Solutions

Abstract: In this work, the electrochemical behavior and passivation of Cu-30Zn alloy in aqueous NaOH solutions was investigated using various electrochemical methods. Potentiodynamic polarization curves showed that increasing NaOH concentration leads to increase corrosion current densities. Mott-Schottky analysis indicated that the passive films displayed p-type semiconductive characteristics and the acceptor densities increased by increasing NaOH concentration, while the flat band potential decreased. Moreover, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…On the other hand, CuO/Cu 2 O nanostructures show high efficiencies in the photodegradation of organic pollutants when compared to that of bare CuO or Cu 2 O nanocrystals. It was reported that the bandgap of a p-type semiconductor CuO is 1.3–1.6 eV, which is lower than the corresponding bandgap of Cu 2 O (2.0 eV) . Very recently, we have reported the visible-light-activated Sonogashira C–C coupling reaction at room temperature catalyzed by single-metal heterogeneous Cu 2 O truncated nanocubes (Cu 2 O TNCs) .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, CuO/Cu 2 O nanostructures show high efficiencies in the photodegradation of organic pollutants when compared to that of bare CuO or Cu 2 O nanocrystals. It was reported that the bandgap of a p-type semiconductor CuO is 1.3–1.6 eV, which is lower than the corresponding bandgap of Cu 2 O (2.0 eV) . Very recently, we have reported the visible-light-activated Sonogashira C–C coupling reaction at room temperature catalyzed by single-metal heterogeneous Cu 2 O truncated nanocubes (Cu 2 O TNCs) .…”
Section: Introductionmentioning
confidence: 99%